2021
DOI: 10.1002/arch.21769
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Metarhizium rileyi evading cellular immune responses in Helicoverpa armigera

Abstract: Upon entry into the hemocoel of host insects, entomopathogenic fungi switch to yeast‐like hyphal bodies that are not recognized by host hemocytes and replicate extensively in the hemolymph. The mechanism by which hyphal bodies evade host cellular immunity is not well understood. This study compares Metarhizium rileyi conidia and hyphal bodies with respect to elicitation of the immune response of Helicoverpa armigera and recognition by host pattern recognition receptors (PRRs). We found that the ability of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Therefore, we conclude that other PRRs, such as CTL3 identified here, may also contribute to the induction of AMPs. However, our previous study showed a lower affinity of βGRPs or CTL3 to M. rileyi hyphal bodies [ 27 ]. Given that ecdysone triggers the expression of many immune-related genes, such as PRRs and AMPs [ 42 , 63 ], an increased 20E titer upon M. rileyi infection may contribute to the upregulation of AMPs, either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conclude that other PRRs, such as CTL3 identified here, may also contribute to the induction of AMPs. However, our previous study showed a lower affinity of βGRPs or CTL3 to M. rileyi hyphal bodies [ 27 ]. Given that ecdysone triggers the expression of many immune-related genes, such as PRRs and AMPs [ 42 , 63 ], an increased 20E titer upon M. rileyi infection may contribute to the upregulation of AMPs, either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the infection of Metarhizium rileyi (also known as Nomuraea rileyi ) impairs and evades cellular immunity in the lepidopteran insect Helicoverpa armigera [ 26 , 27 ]. In the current study, we found that M. rileyi infection stimulated plasma antibacterial activity and enhanced the AMP expression.…”
Section: Introductionmentioning
confidence: 99%
“…lower glucan contents compared to other propagules like submerged conidia and hyphae, which may contribute to their ability to evade host immune responses ( 31 , 50 , 120 , 121 ). For example, hyphal bodies of M. rileyi induce weaker cellular immune responses in the body cavity of Helicoverpa armigera caterpillars compared to M. rileyi conidia ( 122 ). Additionally, EPF express a range of proteins to coat hyphal bodies, camouflaging their cell wall structures to further evade the host insect immunity ( 123 , 124 ).…”
Section: Fungal Penetration and Growth In Hemolymph And Insect Immune...mentioning
confidence: 99%
“…This is due to the reduced number of studies related to immune responses and host defenses to pathogens prior to the 1990s. However, interest in this research area increased from 2012 to 2022, for example, Li et al (2021) described the mechanism of action of M. rileyi in relation to cellular immune responses in H. armigera, concluding that the mechanism by which entomopathogenic fungi escape host cellular immunity involves the inability of hosts to recognize hyphal bodies to induce a cellular immune response.…”
Section: Analysis Of Publication and Distribution Trends In Countriesmentioning
confidence: 99%